2009
DOI: 10.1271/bbb.80813
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Lysophosphatidic Acid, a Wound-Healing Lipid, during Digestion of Cabbage Leaves

Abstract: Lysophosphatidic acid (LPA) is a lipid mediator that plays a role in the process of wound healing in animal tissues, including the digestive tract. We determined LPA in several foodstuffs, and found that cabbage leaves were the richest source of LPA. We also found that, at 22 and 195 nmol/g (wet weight), LPA and phosphatidic acid (PA) were respectively formed during mastication of raw cabbage leaves and that the resulting PA was converted to LPA by pancreatic phospholipase A(2). The lipid extract obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 32 publications
2
65
0
Order By: Relevance
“…Tanaka et al showed that LPAs from cabbage leaf induced the proliferation and migration of 3T3 fibroblasts and also showed that this cell expresses endogenous LPA1, LPA2 and LPA4 receptor subtypes. 7) In addition, LPAs from cabbage increased the migration of the gastric epithelium-like cell line, showed that oral administration of LPA as well as phosphatidic acid attenuates aspirin-induced stomach mucosal injury, further supporting the idea that LPA could be used to attenuate aspirin side-effects in the stomach. 18) In addition, LPAs in soybean lecithin also exhibited anti-gastric ulcer activity.…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 86%
See 2 more Smart Citations
“…Tanaka et al showed that LPAs from cabbage leaf induced the proliferation and migration of 3T3 fibroblasts and also showed that this cell expresses endogenous LPA1, LPA2 and LPA4 receptor subtypes. 7) In addition, LPAs from cabbage increased the migration of the gastric epithelium-like cell line, showed that oral administration of LPA as well as phosphatidic acid attenuates aspirin-induced stomach mucosal injury, further supporting the idea that LPA could be used to attenuate aspirin side-effects in the stomach. 18) In addition, LPAs in soybean lecithin also exhibited anti-gastric ulcer activity.…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 86%
“…5) In addition, Tanaka et al reported that vegetables such as cabbage, broccoli, komatsuna, green soybean, and radish contain LPAs and quantitated the LPA content using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). 7) Among the vegetables, cabbage leaf contains the largest amount of LPAs followed by broccoli, komatsuna, and green soybean. Interestingly, the amount of LPA homologues in cabbage leaf was in the order of LPA C 18:3 >LPA C 16:0 >LPA C 18:2 >LPA C 18:1 .…”
Section: Herbal Medicines As Rich Lpa Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…26) Recently, various types of vegetables including cabbage leaf have been demonstrated to contain significant amounts of LPA. 27) Cabbage leaf was the richest vegetable source of LPA, the major molecular species of which were α-linolenate (18 : 3)-containing species followed by palmitate (16 : 0)-, linoleate (18 : 2)-and oleate (18 : 1)-containing species in that order. 27) …”
Section: Foods and Gastrointestinal Homeostasismentioning
confidence: 98%
“…They also demonstrated by immunohistochemistry the presence of the LPA 2 receptor, the key G-protein coupled receptor involved in the anti-apoptotic response [35], on the luminal surface of rodent gastric epithelial cells (most likely surface mucous cells) and that aspirin-treatment markedly decreased this immunoreactivity. Furthermore, they reported that PA and LPA were present in the gastric contents of rats fed a normal diet, which was expected since these same phospholipids are present in soybean extracts, a usual constituent of rodent chow, and cruciferous vegetables such as cabbage [37]. Tanaka and associates also reported that the activity of phospholipase A 2 (PLA 2 ), which converts PA to LPA in the stomach, was enhanced by bile acids.…”
mentioning
confidence: 89%